2019
DOI: 10.1111/jmp.12419
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia in rhesus macaques (Macaca mulatta): Association with pregnancy and chronic stress

Abstract: Background Alopecia in captive non‐human primates is often presented as a welfare issue. However, it is a complex condition with a number of possible causes. The purpose of this study was to assess the impact of pregnancy and hair cortisol concentrations on alopecia in rhesus macaques. Methods Subjects were 113 socially housed adult female rhesus macaques (27 pregnant, 35 nursing infants, 51 controls). During routine physicals, photographs were taken for alopecia assessment and hair samples were collected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…However, the cause of alopecia was unknown. The bilateral symmetrical alopecia has been described in different macaque species in captivity [1][2][3] , however, based on our knowledge, it has never been described in free-ranging macaques.…”
mentioning
confidence: 99%
“…However, the cause of alopecia was unknown. The bilateral symmetrical alopecia has been described in different macaque species in captivity [1][2][3] , however, based on our knowledge, it has never been described in free-ranging macaques.…”
mentioning
confidence: 99%
“…Research on hair loss disorders in primates has been ongoing for decades with many reported causes, including protein malnutrition, 37,38 toxicities, 32,39‐41 alopecia totalis, 42 white monkey syndrome, 43,44 nutrient deficienciencies,45,46 seborrheic dermatitis, 47 latex hypersensitivity, 36 atopic dermatitis, 35,48 telogen effluvium, 49 alopecia areata universalis, 50 pregnancy, 3,51 and a hairless gene in rhesus macaques infants 52,53 . Psychogenic alopecia on a distal limb has also been reported in rhesus macaques 54 .…”
Section: Discussionmentioning
confidence: 99%
“…and other nonhuman primates (NHPs). Studies have investigated an array of potential contributors to alopecia in NHPs, including stress [ 1 , 2 , 3 , 4 , 5 , 6 ], nutritional deficiencies [ 7 ], chronic inflammation [ 8 ], behavior, such as self-epilation or hair pulling by social partners [ 9 , 10 , 11 ], temperament [ 12 ], and facility of origin [ 2 , 13 , 14 ]. While no one single cause has been identified, there are some correlates consistently found by surveys of alopecia within NHP populations.…”
Section: Introductionmentioning
confidence: 99%
“…First, alopecia has been associated with sex and reproductive status in macaques. Several studies have found that female monkeys, especially pregnant females, typically show higher degrees of hair loss than males [ 3 , 6 , 15 , 16 , 17 , 18 , 19 ]. Dettmer and colleagues [ 17 ] additionally found that among pregnant females, hair cortisol was positively correlated with alopecia and infant birth weight and growth, and Lutz [ 18 ] found that among baboons ( Papio hamadryas spp.…”
Section: Introductionmentioning
confidence: 99%